Adoption of Good Management Practices by Aquafarmers - J.C., Jeeva; S., Balasubramaniam; Srinath, Krishna (Fishery Technology, 2025)
The study was conducted among the aquafarmers in four selected districts viz., Trichur, Alleppey, Ernakulam and Kannur in Kerala. Data were collected on the extent of adoption of good management practices among the sample respondents. Of the 10 practices evaluated, the adoption scores were higher for six practices viz., preparation of ponds (93.15%), eradication of predators and weeds (85.39%), use of PGR tested seeds (84.47%), use of recommended feeding schedule (77.63%), water exchange and quality monitoring (71.69%) and harvesting after prescribed days of culture (70.32%). The extent of adoption of each practice varied significantly (p < 0.01) among the aquafarmers with the overall mean adoption score of 70.09% (n=73). The variables viz., number of training programmes undergone, number of information sources utilized and expert services availed, were found to have positive relationship with the extent of adoption. Regression analysis revealed that of the seven variables, only one variable viz., number of training programmes undergone had contributed significantly (p < 0.05) towards the extent of adoption of improved practices.